(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Construction industry plays vital role in the Indian economy, which is rapidly growing in the current market scenario. The demand of the construction is continuously increasing. The construction time and cost is the major factor in the construction industry, which may affect the delay and other several impacts on the contractor or builder. Secondly the quality of the work finished also required for the client. So its important to maintain the constant quality and services. In these case study the dry wall analysis and technical evaluation is concluded by case study. In these case study the different types of green construction material and their market analysis, comparative analysis between the masonry bricks Vs drywall as by considering the various aspect for the Indian construction. Where the delay and skilled labour is the major concerned for the construction industry.